Exploring the Interaction Between Local Culture and National Inheritance Law in Indonesia: A Qualitative Analysis of Islamic Fiqh and Civil Law - Sarmadi, Akhmad Sukris (Indonesian Research Journal on Education, 2024)
The protection of inheritance rights within local cultures in Indonesia faces challenges due to the coexistence of customary, Islamic, and Western civil inheritance law systems. Despite the constitutional enforceability of national inheritance law, there may be gaps in how it accommodates the various local cultural inheritance systems, as evidenced by dissatisfaction among Muslims regarding the enforcement of Islamic inheritance law. This study aims to analyze the interaction between local culture and national inheritance law in Indonesia using a qualitative research design. The main source materials in Islamic fiqh and Islamic civil law were analyzed through a qualitative content analysis conducted manually by the researcher. The analysis revealed several patterns and themes, providing valuable insights into the research question and uncovering important nuances and complexities within the subject matter. The protection of inheritance rights within local cultures encounters various challenges, ranging from the impact of globalization and industrialization on traditional practices to the complexities of legal frameworks and the need for cultural education and awareness. The preservation of cultural expressions and heritage also plays a crucial role in promoting social cohesion and fostering a sense of community identity. The results of this research could potentially inform future policy decisions and help create a more equitable inheritance system in Indonesia that is both protective and representative of its diverse cultural inheritance systems.